Physiological Mechanisms of Exercise and Its Effects on Postural Sway: Does Sport Make a Difference? - Zemková, Erika (Frontiers in Physiology, 2022)
While the effect of a variety of exercises on postural balance control has been extensively studied, less attention has been paid to those requiring sport-specific skills. Therefore there is a need to analyse the literature and elucidate changes in postural balance control after exercises performed in conditions close to a particular sport. This scoping review aims (i) to map the literature that addresses postural sway aspects of acute responses to general and sport-specific exercises and their underlying physiological mechanisms, and (ii) to identify gaps in the existing literature and propose future research on this topic. The main literature search conducted on MEDLINE, Web of Science, Scopus, PubMed and Cochrane Library databases was completed by SpringerLink, Elsevier and Google Scholar. A total of 60 articles met the inclusion criteria. Findings identified that among a variety of studies evaluating the effects of exercise on postural balance control, only few of them were conducted under sport-specific conditions (i.e., while shooting in biathlon or pentathlon, and after simulated or match-induced protocols in combat and team sports). Therefore, more research is still needed to address this gap in the literature and aim research at investigation of postural sway response to sport-specific exercises. Further analysis of the literature showed that the type, intensity and duration of exercise play a key role in increased postural sway. Whole body and localized muscular fatigue of the trunk, neck and lower limbs is considered to be a main factor responsible for the magnitude of balance impairment in an initial phase of recovery and speed of its readjustment to a pre-exercise level. Other likely factors affecting postural stability are hyperventilation and deterioration of sensorimotor functions, though some contribution of muscle damage, dehydration, hyperthemia or dizziness cannot be excluded. A better understanding of the physiological mechanisms of balance impairment after exercises performed under simulated fatigue induced protocols close to conditions specific to a particular sport, has implications for designing smart exercise programs tailored to individual needs to improve athlete performance with high demands on postural stability and/or decrease their risk of injuries.